A Simplified Amino Acidic Alphabet to Unveil the T-Cells Receptors Antigens: A Computational Perspective - Iannuzzi, Raffaele; Rossetti, Grazisa; Spitaleri, Andrea; Bonnal, Raoul J. P.; Pagani, Massimiliano; Mollica, Luca (Frontiers in Chemistry, 2021)
The exposure to pathogens triggers the activation of adaptive immune responses through antigens bound to surface receptors of antigen presenting cells (APCs). T cell receptors (TCR) are responsible of initiating the immune response through their physical direct interaction with antigen-bound receptors on the APCs surface. The study of T cells interactions with antigens is considered of crucial importance for the comprehension of the role of immune responses in cancer growth and for the subsequent design of immunomodulating anticancer drugs. RNA sequencing experiments performed on T cells represented a major breakthrough for this branch of experimental molecular biology. Apart from the gene expression levels, the hypervariable CDR3 sequences of the TCR loops can now be easily determined and modelled in the three dimensions, being the portions of TCR mainly responsible for the interaction with APC receptors. The most direct experimental method for the investigation of antigens would be based on peptide libraries, but their huge combinatorial nature, size, cost and the difficulty of experimental fine tuning makes this approach complicated as well as time and money consuming. We have implemented and in silico methodology with the aim of moving from CDR3 sequences down to a library of potentially antigenic peptides that can be used in immunologically oriented experiments in order to study T cells reactivity. In order to reduce the size of the library, we have verified the reproducibility of experimental benchmarks using the permutation of only six residues that can be considered representative of all the ensemble of 20 natural amino. Such a simplified alphabet is able to correctly find the poses and chemical nature of original antigens within a small subset of ligand of potential interest. The newly generated library would have the advantage of heading to potentially antigenic ligands that would contribute to a better understanding of the chemical nature of TCR-antigen interactions. This step is crucial in the design of immunomodulators targeted towards T-cells response as well as in understanding the first principles of immune response in several diseases from cancer to autoimmune disorders.